The use of polygraph for recruitment: a case of loophole in colombia - López Cortés, Oscar (University Santo Tomás, Bogotá, 2016)
This article analyzes the use of polygraph for recruitment, subject that there is a loophole about thisin Colombia. The question inquires if in accordance to human dignity principle and FundamentalRights at Work is possible to use the polygraph for recruitment or not. Therefore, the Colombianlegal frame about polygraph will be reconstructed; later three axiological arguments that will allowto reasonably conclude that the polygraph use for recruitment is not constitutional will be exposed.